2010
DOI: 10.1016/j.ijdevneu.2010.10.007
|View full text |Cite|
|
Sign up to set email alerts
|

Neurochemical evidence that 3‐methylglutaric acid inhibits synaptic Na+,K+‐ATPase activity probably through oxidative damage in brain cortex of young rats

Abstract: 3-Methylglutaconic aciduria (MGTA) comprehends a group of disorders biochemically characterized by accumulation of 3-methylglutaric acid (MGA), 3-methylglutaconic acid (MGT) and occasionally 3-hydroxyisovaleric acid (OHIVA). Although neurological symptoms are common in the affected individuals, the mechanisms of brain damage are poorly known. In the present study we investigated the in vitro effect MGA, MGT and OHIVA, at concentrations ranging from 0.1 to 5.0mM, on bioenergetics and oxidative stress in synapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 69 publications
(74 reference statements)
1
13
1
Order By: Relevance
“…In this study, using synaptosomes of cerebral cortex from young rats, the authors found reduced mitochondrial function, increased ROS formation and inhibition of the Na + ,K + -ATPase enzyme activity, but no changes in lipid peroxidation were observed. Thus, our present study represents a logic extension of the one from Ribeiro et al [20] and confirms part of the effects previously described for the toxic pattern of 3MGA. Interestingly, in contrast to that study we found changes in the levels of TBARS at concentrations of 1 and 5 mM.…”
Section: The Toxic Synergism Induced By 3mga and Quin Was Prevented Asupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, using synaptosomes of cerebral cortex from young rats, the authors found reduced mitochondrial function, increased ROS formation and inhibition of the Na + ,K + -ATPase enzyme activity, but no changes in lipid peroxidation were observed. Thus, our present study represents a logic extension of the one from Ribeiro et al [20] and confirms part of the effects previously described for the toxic pattern of 3MGA. Interestingly, in contrast to that study we found changes in the levels of TBARS at concentrations of 1 and 5 mM.…”
Section: The Toxic Synergism Induced By 3mga and Quin Was Prevented Asupporting
confidence: 93%
“…5b) and MTT reduction (Fig. 5c) were estimated as endpoints of the toxicity exerted by the synergic action of 3MGA and QUIN The toxic model induced by 3MGA and used in the present work was previously validated in synaptosomes by Ribeiro et al [20]. In this study, using synaptosomes of cerebral cortex from young rats, the authors found reduced mitochondrial function, increased ROS formation and inhibition of the Na + ,K + -ATPase enzyme activity, but no changes in lipid peroxidation were observed.…”
Section: The Toxic Synergism Induced By 3mga and Quin Was Prevented Amentioning
confidence: 99%
“…,K ? -ATPase in rat brain and this effect was associated with an increased free radical generation [35]. So, in this work, we aimed to investigate oxidative stress parameters in biological fluids from HMGA patients and verify if the therapy with protein restriction and L-carnitine could exert some influence on this process.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the transcriptome of symptomatic, clinically severe MCC deficiency and neurological studies on the cerebral cortex of young rats [55][56][57][60][61][62][63][64][65], this marginal MCC deficiency skin fibroblast transcriptome also had a genetic footprint suggestive of partial mitochondrial dysfunction, oxidative stress and disruption of energy homeostasis. Transcripts of mitochondrial respiratory chain complexes I, II and IV were significantly differentially expressed (Table 4) affecting the OXPHOS system (NDUFS2, SDHD, MT-CO1/COX1, COX6 and COX17).…”
Section: Discussionmentioning
confidence: 61%
“…Imbalances in eicosanoid metabolism signalling have been detected in individuals with a weak tolerance to environmental factors and susceptibility to environmental stressors that often result in asthma [94][95][96][97], allergy, eczema [98][99][100], arthritis [81] as well as the development of cancer [73] and might also play a role in the development of non-specific symptoms of marginal MCC deficiency. Therefore, life-long monitoring of ROS levels of individuals with MCC deficiency along with the administration of anti-oxidants to prevent and manage deleterious secondary signalling responses may be beneficial as previously proposed (Figure 3) [55,56,60,64,65,101].…”
Section: Discussionmentioning
confidence: 96%